2010
DOI: 10.1074/jbc.m110.113035
|View full text |Cite
|
Sign up to set email alerts
|

A Proprotein Convertase Subtilisin-like/Kexin Type 9 (PCSK9) C-terminal Domain Antibody Antigen-binding Fragment Inhibits PCSK9 Internalization and Restores Low Density Lipoprotein Uptake

Abstract: PCSK9 binds to the low density lipoprotein receptor (LDLR) and leads to LDLR degradation and inhibition of plasma LDL cholesterol clearance. Consequently, the role of PCSK9 in modulating circulating LDL makes it a promising therapeutic target for treating hypercholesterolemia and coronary heart disease. Although the C-terminal domain of PCSK9 is not involved in LDLR binding, the location of several naturally occurring mutations within this region suggests that it has an important role for PCSK9 function. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 30 publications
4
77
0
Order By: Relevance
“…2 and 3). Consequently, this PCSK9 variant no longer affects the downregulation of cell surface LDLR through the endosomal/lysosomal pathway, a major route for PCSK9-mediated LDLR degradation (40 ). Our cell biology findings are consistent with the findings of our human studies, in which individuals carrying the PCSK9-Q152H mutation showed very low plasma PCSK9 concentrations (Ͼ79% reduction compared with the general Canadian population) and consequently low concentrations of circulating LDLC owing to the upregulation of liver LDLR.…”
Section: Discussionsupporting
confidence: 81%
“…2 and 3). Consequently, this PCSK9 variant no longer affects the downregulation of cell surface LDLR through the endosomal/lysosomal pathway, a major route for PCSK9-mediated LDLR degradation (40 ). Our cell biology findings are consistent with the findings of our human studies, in which individuals carrying the PCSK9-Q152H mutation showed very low plasma PCSK9 concentrations (Ͼ79% reduction compared with the general Canadian population) and consequently low concentrations of circulating LDLC owing to the upregulation of liver LDLR.…”
Section: Discussionsupporting
confidence: 81%
“…These fi ndings, combined with the fact that decreased PCSK9 activity is associated with lower LDL-C levels and a reduced risk of coronary heart disease ( 18 ), support the inhibition of PCSK9 as a target of great signifi cance. In fact, several agents are already being investigated in humans (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…1A ) ( 57,58 ). Pcsk9 Ϫ / Ϫ mice exhibit increased hepatic LDLR levels leading to lower circulating cholesterol levels ( 26 ). However, it is unclear if PCSK9 also infl uences the levels of circulating cholesterol independent of the LDLR ( 47 ).…”
Section: Ldlr Is the Predominant Means For Pcsk9-mediated Regulation mentioning
confidence: 99%
“…Whether this disproportionate reduction in risk is due to PCSK9 having a direct negative effect at the atherosclerotic lesion or if the additional benefi t is driven by a modest lifelong reduction in serum cholesterol is unclear. These observations have led to the development of PCSK9 inhibitors as a means to therapeutically reduce LDL-C and the associated CVD risk (25)(26)(27)(28)(29). Inhibition of PCSK9 by monoclonal antibodies, adnectins, or siRNAs reduces LDL-C levels in patients, and clinical trials designed to assess the effect of anti-PCSK9 therapies on cardiovascular outcomes are underway (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42).…”
Section: In Vivomentioning
confidence: 99%